Technical prerequisites and imaging protocols for dynamic and dual energy myocardial perfusion imaging. Issue 12 (December 2015) - Cannaò, Paola M.; Schoepf, U. Joseph; Muscogiuri, Giuseppe; Wichmann, Julian L.; Fuller, Stephen R.; Secchi, Francesco; Varga-Szemes, Akos; De Cecco, Carlo N.
Highlights: CTMPI offers possibility to detect presence of perfusion defects in myocardium. Two techniques available: static and dynamic CT myocardial perfusion imaging. Combination of CCTA and CTMPI can improve ability of CT to detect relevant CAD. Abstract: Coronary CT angiography (CCTA) is an established imaging technique used for the non-invasive morphological assessment of coronary artery disease. As in invasive coronary angiography, CCTA anatomical assessment of coronary stenosis does not adequately predict hemodynamic relevance. However, recent technical improvements provide the possibility of CT myocardial perfusion imaging (CTMPI). Two distinct CT techniques are currently available for myocardial perfusion assessment: static CT myocardial perfusion imaging (sCTMPI), with single- or dual-energy modality, and dynamic CT myocardial perfusion imaging (dCTMPI). The combination of CCTA morphological assessment and CTMPI functional evaluation holds promise for achieving a comprehensive assessment of coronary artery anatomy and myocardial perfusion using a single image modality.